2020
DOI: 10.1111/trf.15771
|View full text |Cite
|
Sign up to set email alerts
|

Zika virus and its implications on cord blood banking and transplantation

Abstract: KEY IDEAS Umbilical cord blood is an important cellular therapy product used for hematopoietic stem cell transplantation, but the US Food and Drug Administration guidance regarding donor screening to reduce the risk of Zika transmission has decreased the number of licensed, eligible cord blood units available for transplantation. There is a crucial need for updated travel risk assessment for Zika virus transmission, validated screening tests for Zika virus in umbilical cord blood, and further research on Zika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…These CBUs were discarded and not used in transplant. 19 , 20 Another study by the National Cord Blood Program, a public CBB, at New York Blood Center found that 27.5% of units collected from March 2016-December 2018 were ineligible for licensure, and, of these, 76% CBUs were ineligible due to ZIKV-related risk factors. 19 , 21 Of the 196 respondents to a 1-year follow-up survey sent to donors who had ZIKV risk, all mothers reported their infants were healthy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These CBUs were discarded and not used in transplant. 19 , 20 Another study by the National Cord Blood Program, a public CBB, at New York Blood Center found that 27.5% of units collected from March 2016-December 2018 were ineligible for licensure, and, of these, 76% CBUs were ineligible due to ZIKV-related risk factors. 19 , 21 Of the 196 respondents to a 1-year follow-up survey sent to donors who had ZIKV risk, all mothers reported their infants were healthy.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 Another study by the National Cord Blood Program, a public CBB, at New York Blood Center found that 27.5% of units collected from March 2016-December 2018 were ineligible for licensure, and, of these, 76% CBUs were ineligible due to ZIKV-related risk factors. 19 , 21 Of the 196 respondents to a 1-year follow-up survey sent to donors who had ZIKV risk, all mothers reported their infants were healthy. 19 This and the current study supports that there are a large number of ineligible CBUs due to ZIKV risk despite lack of reported transmission when these CBUs are used under an IND.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that most publications employ molecular biology for the diagnosis of these infectious entities in the immunosuppressed population. The diagnosis based on serology is still little used because it can present a cross-reaction of antibodies developed in response to other flavivirus infections (yellow fever virus, Japanese encephalitis virus, St Louis encephalitis) and other non-flavivirus viruses such asOropouche, Mayaro, and Chikungunya [11][12][13][14][15]. Because the yellow fever vaccine contains attenuated viruses, a cross-reaction of vaccine antibodies may occur with other viruses of the same genus, such as DENV and ZKV.…”
mentioning
confidence: 99%